Home and family in cognitive rehabilitation after brain injury: Implementation of social reserves. - Mogensen, Jesper; Wulf-Andersen, Camilla (NeuroRehabilitation, 2017)
The focus of the present article is the home and family environment of patients suffering acquired brain injury. In order to obtain the optimal outcome of posttraumatic cognitive rehabilitation it is important (a) to obtain a sufficient intensity of rehabilitative training, (b) to achieve the maximum degree of generalization from formalized training to the daily environment of the patient and (c) to obtain the best possible utilization of "cognitive reserves" in the form of cognitive abilities and "strategies" acquired pretraumatically. Supplementing the institution-based cognitive training with (potentially computerbased) home-based training these three goals may more easily be met. Home-based training supports a higher intensity of training. Training in the home environment also allows better utilization of cognitive strategies acquired pretraumatically and more direct transfer of training results from formalized training to activities of daily living of the patient.